Implementasi model pembelajaran Team Games Tournament pada pembelajaran IPS - Wulandari, Rena Dwi; Ardhian, Trio; Marwanti, Endah; Setyawan, Arya Dani (Universitas Sarjanawiyata Tamansiswa, 2024)
This research examines the application of the Teams Games Tournament learning model using descriptive qualitative research methods. Data collection instrument techniques are observation, interviews and documentation. The validity of the data in this research uses a credibility test by increasing persistence and source triangulation, technical triangulation and time triangulation. The data analysis technique uses the Miles and Huberman model which consists of data collection, data reduction, data presentation and conclusions. The results of the research show that the Team Games Tournament learning model in social studies learning is implemented well through three stages, namely the learning planning stage, the learning implementation stage, and finally the learning assessment or evaluation stage.